Convergence patterns in accounting regulation: Six country cases of the transforming regulatory landscape - Jochen Zimmermann; Jan-Philipp Kilian; Johannes Schymczyk (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
This paper inquires into recent changes of accounting regulation in six OECD countries: Germany, France, England, USA, Canada and Japan. Having formerly been embedded into different institutional environments, accounting systems varied widely in the heyday of the interventionist nation state. Since then, international harmonisation has been transforming national accounting systems, leading to increasing convergence between the various systems. It is the aim of this paper to describe these changes systematically, estimate the degree of international convergence and assess how different institutional origins affect convergence patterns. We develop a framework for comparing accounting systems and identify four criteria that describe the anatomy of a national accounting system: (1) Predominant uses of accounting, (2) Extent of professional self-regulation, (3) Legal backing and (4) Degree of internationalisation. Our findings indicate that global convergence in accounting regulation exists, although limited variations between nation states still remain and depend upon the prevailing national institutional arrangements, which have not (yet) converged. – – Gegenstand des vorliegenden Arbeitspapieres ist die Aufarbeitung des Wandels der Regulierung von Rechnungslegung vom goldenen Zeitalter des Nationalstaats bis heute. Dies erfolgt für die sechs größten OECD Staaten, Deutschland, Frankreich, das Vereinigte Königreich als EU-Fälle und die Vereinigten Staaten, Kanada und Japan als Fälle außerhalb der EU. Traditionell unterscheiden sich die Rechnungslegungssysteme in diesen Ländern aufgrund ihrer Einbindung in institutionelle Rahmenbedingungen wie etwa dem Finanz- oder Rechtssystem. Ziel des Arbeitspapieres ist es zu untersuchen, in welchem Umfang es durch die internationalen Harmonisierungsbemühungen zu einer Konvergenz der Rechnungslegung gekommen ist und wie der Anpassungsprozess durch die unterschiedlichen institutionellen Arrangements beeinflusst wurde. Die Darstellung der Entwicklungen erfolgt anhand von vier Kategorien: (1) dem vorherrschenden Rechnungszweck, (2) dem Ausmaß an (staatsfreier) Selbstregulierung, (3) der rechtlichen Absicherung und (4) dem Grad an Internationalisierung der Rechnungslegung. Unsere Ergebnisse deuten auf eine Konvergenz in weiten Teilen der Regulierung von Rechnungslegung hin. Diese werden jedoch vom Fortbestehen nationaler Präferenzen insbesondere im Bereich der Anspruchsbemessung begleitet.
Keywords: 330; Bilanzrecht; International Financial Reporting Standards; Governance-Ansatz; Deutschland; Frankreich; Großbritannien; USA; Kanada; Japan